Awareness on Neonatal Care Among Rural Mothers of Reproductive Age Group Admitted in A Tertiary Level Hospital at Mymensingh (Anwer Khan Modern Medical College Journal, 2017)
Background: In Bangladesh the neonatal mortality rate is unacceptably high, at 48.4 per 1,000 live births and it is higher in rural areas while the neonatal mortality rate in Asia is 41 per 1,000 live-births, compared to 7 per 1,000 live-births in developed countries.Methodology: This descriptive type of cross sectional study was carried out among 180 rural mothers of reproductive age in Mymensingh Medical College Hospital, Mymensingh from October 2013 to January 2014. Data were collected on a pretested questionnaire by face to face interview. Data were analyzed manually and by using computer.Results: The study revealed that 50.6% of the respondents were housewife & education wise 42.2% had primary education with mean age 26.28 ±5.50 years. 61% respondents knew that cord should be cut by sterile blade and 65% respondents mentioned that cord should be cut immediate after delivery. Among them 44.4% knew about initiation of breast feeding within 1st hour of delivery, 71.1% believed the importance of colostrums feeding. Only 30% of the respondents knew about frequency of breast feeding to the baby should be 8-10 times in a day and 58% had knowledge on exclusive breast feeding. Of the respondents 52.2% went for exclusive breast feeding but others did not. 67% respondents immunized their baby whereas 33% did not. More than half of the respondents (59%) cleaned their breast before feeding and 80.6% respondents washed their hands before handling their newborn. A significant association was found between education and knowledge on immunization of newborn (P=0.000), education and exclusive breast feeding (P=0.003).Conclusion: The current study may boost up the awareness among rural mothers of reproductive age group on neonatal care which will further encourage them to be educated and thus neonatal morbidity & mortality may decline in some extent.Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 14-19